Exploring Learners’ Autonomy in the Online Translation Class - Yansyah Yansyah; Melly Thania (Eduinfo Media, 2020)
Raising learners’ autonomy is demanded in today’s education. The more autonomous the learners, the better the result of the learning outcomes. This paper elaborates the findings from a case study on the development of learners’ autonomy in an online translation class. One teacher and five students were invited to be the participants to share their perspectives and experiences during the course. The data were gathered through an in-depth interview with both the teacher and learners. The findings revealed that the use of Google Classroom as a media of learning was quite effective. Most of the students became more autonomous in learning the materials, but some challenges such as late submission for the assignment, lack of motivation to learn, and some limitations of online learning still emerged during the implementation.